DAPTASI PEDAGANG PASCA KEBAKARAN DI PASAR ATAS KOTA BUKITTINGGI - Zaki Ananda; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
asar Atas is one of the tourist icons in the city of Bukittinggi, which is the driving force for the economy of the surrounding community. This research was conducted in the city of Bukittinggi. The purpose of this study is to find out the adaptation strategies carried out by traders and also the obstacles faced by traders in the Atas market of Bukittinggi city. In this study, the technique of taking the subject was using purposive sampling which had determined the criteria in this study. The theory used in this study uses the theory of social action (rational Instrumental) proposed by Max Weber. This study uses a qualitative approach with a descriptive type. To obtain relevant research results, the researcher conducted interviews with 16 subjects and also made direct observations in the field. The results of this study are there are 3 strategies used in adapting and the obstacles faced by traders. The first strategy used is an active strategy, by exploiting all existing potential sources, the second strategy is a passive strategy, namely, by minimizing spending, and the last strategy is a network strategy, namely, by utilizing the social network that is owned. The obstacles faced by traders are the lack of capital to start the business again, the less strategic location of the kiosk. Keywords: Traders, Adaptation Strategy, Bukittinggi City